Urelumab alone or in combination with rituximab in patients with relapsed or refractory B‐cell lymphoma - John M. Timmerman; Charles Herbaux; Vincent Ribrag; Andrew D. Zelenetz; Roch Houot; Sattva S. Neelapu; Theodore F. Logan; Izidore S. Lossos; Walter J. Urba; Gilles Salles; Radhakrishnan Ramchandren; Caron A. Jacobson; et al. (2020)
Urelumab, a fully human, non-ligand binding, CD137 agonist IgG4 monoclonal antibody, enhances T-cell and natural killer-cell antitumor activity in preclinical models, and may enhance cytotoxic activity of rituximab. Here we report results in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), and other B-cell lymphomas, in phase 1 studies evaluating urelumab alone (NCT01471210) or combined with rituximab (NCT01775631). Sixty patients received urelumab (0.3 mg/kg IV Q3W, 8 mg IV Q3W, or 8 mg IV Q6W); 46 received urelumab (0.1 mg/kg, 0.3 mg/kg, or 8 mg IV Q3W) plus rituximab 375 mg/m2 IV QW. The maximum tolerated dose (MTD) of urelumab was determined to be 0.1 mg/kg or 8 mg Q3W after a single event of potential drug-induced liver injury occurred with urelumab 0.3 mg/kg. Treatment-related AEs were reported in 52% (urelumab: grade 3/4, 15%) and 72% (urelumab + rituximab: grade 3/4, 28%); three led to discontinuation (grade 3 increased AST, grade 4 acute hepatitis [urelumab]; one death from sepsis syndrome [urelumab plus rituximab]). Objective response rates/disease control rates were 6%/19% (DLBCL, n = 31), 12%/35% (FL, n = 17), and 17%/42% (other B-cell lymphomas, n = 12) with urelumab and 10%/24% (DLBCL, n = 29) and 35%/71% (FL, n = 17) with urelumab plus rituximab. Durable remissions in heavily pretreated patients were achieved; however, many were observed at doses exceeding the MTD. These data show that urelumab alone or in combination with rituximab demonstrated manageable safety in B-cell lymphoma, but the combination did not enhance clinical activity relative to rituximab alone or other current standard of care.